2016
DOI: 10.1007/s40825-016-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Diesel Particulate Filter Failure During Commercial Fleet Use due to Pinholes, Melting, Cracking, and Fouling

Abstract: Diesel particulate filters (DPFs) are essential particulate matter emission control devices. Some diesel particulate filters have been observed to fail during industrial-fleet vehicle use. DPFs that fail during vehicle use compromise particulate matter emission capture. Herein, failures in cordierite DPF substrates observed during commercial fleet use were characterized as pinhole failure, melt failure, crack failure, and fouling failure. The observed failures were correlated to particulate matter chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…The results of simulation showed that the combustion of soot causes a high temperature rise in the filter which would affect the durability of DPF. Uncontrolled combustion during Fuel based regeneration will result in failure of DPF by formation of cracks, melts and pinholes [1].…”
Section: Commercial Fuel Based Active Regeneration Of Dpfmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of simulation showed that the combustion of soot causes a high temperature rise in the filter which would affect the durability of DPF. Uncontrolled combustion during Fuel based regeneration will result in failure of DPF by formation of cracks, melts and pinholes [1].…”
Section: Commercial Fuel Based Active Regeneration Of Dpfmentioning
confidence: 99%
“…Diesel engines are considered as second leading anthropogenic source of particulate matter (PM2.5 and PM10) which is formed due to combustion of fuel and lubricating oil [1]. The exhaust emission from diesel engine includes carbon monoxide, nitrates, hydrocarbons and particulate matter [2].…”
Section: Introductionmentioning
confidence: 99%
“…x Oxygen (Equations (2) and (3)) is the oxygen mole fraction in the gas phase, m total (Equation (2)) is the local concentration of soot (all the soot present in the system), and m catalyzed (Equation 3) is the local concentration of soot in contact with the catalyst. The values of the kinetic parameters for Equations (2) and 3are given in Table 1. Table 1.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Catalytic (i.e., catalyst-coated) diesel particulate filters (DPFs) have been proposed to allow regeneration (i.e., oxidation of soot) at low temperatures [1], thus overcoming the drawbacks of the thermal process, including the formation of excessively hot regions that may cause irreversible damage to the filter [2].…”
Section: Introductionmentioning
confidence: 99%
“…The DPF peak temperature and the maximum temperature gradient during active regeneration are vital for the DPF, because both of them should be controlled within the safety limits of the DPF substrate material to avoid melting or cracking of the DPF. 27 In this study, the DPF temperature field during active regeneration was measured. Theoretically, the circumferential temperature distribution should be uniform if the flow uniformity of the aftertreatment system has been well optimized.…”
Section: Experimental Setup and Test Proceduresmentioning
confidence: 99%